Identifying the Causes of Dissatisfaction of Construction Labour: A Case Study of Building Construction of Jajarkot District Hospital, Nepal - Bista, Bikash; Neupane, Uttam; Bhattarai, Subash Kumar (Himalayan Journal of Applied Science and Engineering, 2024)
The construction industry in Nepal is a significant contributor to the country’s economy, but it faces challenges related to construction labor’s dissatisfaction. This study focuses on identifying the causes of dissatisfaction of construction labour during the building construction in Jajarkot. The primary objective of this study is to pinpoint and dissect the critical challenges that confront construction workers and, more importantly, to propose strategies aimed at enhancing their job satisfaction. The ultimate goal is to catalyse improvements in overall productivity and the successful completion of construction projects in the region. The study uses a mixed-method approach, including questionnaire, reports and research papers to gather data. The research identifies several key factors contributing to labour dissatisfaction, including delayed payment, inadequate compensation, inadequate wages, unsafe working conditions, excessive working hours and insufficient safety measures. These issues have a direct impact on construction labour motivation, affects their morale and well-being, leading to unhappiness, reduced productivity and reduced work excellence. The key recommendations include timely payments, improving compensation, enhancing working conditions, offering career growth prospects, promoting open communication, and recognizing workers’ contributions. By adopting these measures, the construction industry can foster a positive work environment, leading to increased productivity and timely project completion.